Functional Characterization of a Magnesium Transporter of Root Endophytic Fungus Piriformospora indica - Prasad, Durga; Verma, Nidhi; Bakshi, Madhunita; Narayan, Om Prakash; Singh, Alok Kumar; Dua, Meenakshi; Johri, Atul Kumar (Frontiers in Microbiology, 2019)
Magnesium (Mg) is a crucial macronutrient required for the regular growth of plants. Here we report the identification, isolation and functional characterization of Mg-transporter PiMgT1 in root endophytic fungus Piriformospora indica. We also report the role of P. indica in the improvement of the Mg nutrition of the plant particularly under Mg deficiency condition. Protein BLAST (BLASTp) for conserved domains analysis showed that PiMgT1 belong to CorA like protein family of bacteria. We have also observed the presence of conserved ‘GMN’ signature sequence which suggests that PiMgT1 belongs to Mg transporter family. Phylogenetic analysis revealed that PiMgT1 clustered among fungal CorA family members nearer to basidiomycetes. Functionality of PiMgT1 was confirmed by complementation of a yeast magnesium transporter mutant CM66. We have observed that PiMgT1 restored the growth of mutant and showed comparable growth with that of WT. We found statistically significant (p<0.05) two folds increase in the total intracellular Mg content of mutant complemented with PiMgT1 as compared to the mutant. These observations suggest that PiMgT1 is actively involved in Mg uptake by the fungus and may be helping in the nutritional status of the host plant.